2011
DOI: 10.1007/dcr.0b013e3182051d96
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Analysis of Cosmesis, Morbidity, and Patient Satisfaction Following Limberg Flap for the Treatment of Sacrococcygeal Pilonidal Sinus

Abstract: Initial wound closure and low recurrence rates after treatment with Limberg flap in pilonidal sinus disease lead to high patient satisfaction. The cosmetic outcome is acceptable, but an issue for some patients. These results support the use of the Limberg flap in complex pilonidal sinus disease after carefully informing patients about the cosmetic consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 28 publications
0
25
1
2
Order By: Relevance
“…The operation time was 40.3 ± 4.4 min in our flap technique. The overall complication rate ranges from 0.8% to 25.7% in full-thickness flap procedures, while Krand et al reported a rate of 7.2% [4, 18, 20, 22]. In the present study, the total complication rate was 4.8%.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…The operation time was 40.3 ± 4.4 min in our flap technique. The overall complication rate ranges from 0.8% to 25.7% in full-thickness flap procedures, while Krand et al reported a rate of 7.2% [4, 18, 20, 22]. In the present study, the total complication rate was 4.8%.…”
Section: Discussioncontrasting
confidence: 42%
“… Figure 4 shows the mapping schemes for the Limberg, Dufourmentel, and modified Dufourmentel flaps. The operation times were ranged between 40.0 and 57.4 min for full-thickness flap procedures, such as the Limberg and Dufourmentel flaps, while it was 42.8 ± 4.2 min in reconstruction of S-type incisions with the advancement flap described by Krand et al [4, 2022]. The operation time was 40.3 ± 4.4 min in our flap technique.…”
Section: Discussionmentioning
confidence: 74%
“…However, the treatment regimen should ideally minimize pain, allow short hospitalization time, reduce complications and rate of recurrence and should provide rapid recovery and return to normal daily activities [3]. There are several surgical procedures described for the treatment of pilonidal sinus disease including incision and drainage, excision and healing by second intention, which is currently the most commonly used procedure [4][5][6], excision and primary closure, excision with reconstructive flap techniques [7], however, the effectiveness of excision and primary closure in the treatment of pilonidal sinus disease is highly debated since it is associated with a high rate of recurrence. This can be due to the midline scar left from the procedure which further triggers the accumulation of loose hair, which is the original cause of pilonidal sinus formation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…When performed adequately, it will generate a good functional result with the coverage of a skin defect and it also provides an acceptable cosmetic result (3). A Limberg plastic surgery procedure should only be performed in infection-free wound conditions to avoid a flap infection (4).…”
Section: Sirmentioning
confidence: 99%